Lebrikizumab in moderate-to-severe asthma: pooled data from two randomised placebo-controlled studies. Issue 8 (22nd May 2015) - Hanania, Nicola A; Noonan, Michael; Corren, Jonathan; Korenblat, Phillip; Zheng, Yanan; Fischer, Saloumeh K; Cheu, Melissa; Putnam, Wendy S; Murray, Elaine; Scheerens, Heleen; Holweg, Cecile TJ; Maciuca, Romeo; et al.
Abstract : Introduction: In a subset of patients with asthma, standard-of-care treatment does not achieve disease control, highlighting the need for novel therapeutic approaches. Lebrikizumab is a humanised, monoclonal antibody that binds to and blocks interleukin-13 activity. Methods: LUTE and VERSE were replicate, randomised, double-blind, placebo-controlled studies, evaluating multiple doses of lebrikizumab in patients with uncontrolled asthma despite the use of medium-to-high-dose inhaled corticosteroid and a second controller. Patients received lebrikizumab 37.5, 125, 250 mg or placebo subcutaneously every four weeks. The primary endpoint was the rate of asthma exacerbations during the placebo-controlled period. Analyses were performed on prespecified subgroups based on baseline serum periostin levels. Following the discovery of a host-cell impurity in the study drug material, protocols were amended to convert from phase III to phase IIb. Subsequently, dosing of study medication was discontinued early as a precautionary measure. The data collected for analysis were from a placebo-controlled period of variable duration and pooled across both studies. Results: The median duration of treatment was approximately 24 weeks. Treatment with lebrikizumab reduced the rate of asthma exacerbations, which was more pronounced in the periostin-high patients (all doses: 60% reduction) than in the periostin-low patients (all doses: 5% reduction); no dose–response was evident. Lung function also improved following lebrikizumab treatment, with greatest increase in FEV1 in periostin-high patients (all doses: 9.1% placebo-adjusted improvement) compared with periostin-low patients (all doses: 2.6% placebo-adjusted improvement). Lebrikizumab was well tolerated and no clinically important safety signals were observed. Conclusions: These data are consistent with, and extend, previously published results demonstrating the efficacy of lebrikizumab in improving rate of asthma exacerbations and lung function in patients with moderate-to-severe asthma who remain uncontrolled despite current standard-of-care treatment. Trial registration numbers: The LUTE study was registered under NCT01545440 and the VERSE study under NCT01545453 at http://www.clinicaltrials.gov